1999
DOI: 10.1034/j.1399-6576.1999.430817.x
|View full text |Cite
|
Sign up to set email alerts
|

Convulsions and respiratory arrest in association with desmopressin administration for the treatment of a bleeding tonsil in a child with borderline haemophilia

Abstract: Desmopressin (DDAVP) may be used to augment the action of factor VIII in mild haemophilia. Its use has been associated with serious adverse effects. We report a case of a three-year-old child with a family history of haemophilia who suffered complications due to severe acute hyponatraemia following the administration of this drug for post-tonsillectomy bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 11 publications
(22 reference statements)
0
15
0
Order By: Relevance
“…Thirteen publications that utilized desmopressin for AT procedures in patients with mild bleeding disorders were identified and are summarized in Table 1. This included 144 patients aged 16 months to 45 years [5,[9][10][11][12][13][14][15][16][17]. DDAVP dosing was the standard 0.3 lg kg )1 in all patients except in the first experience by Mannucci, who utilized 0.5 lg kg )1 [5].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirteen publications that utilized desmopressin for AT procedures in patients with mild bleeding disorders were identified and are summarized in Table 1. This included 144 patients aged 16 months to 45 years [5,[9][10][11][12][13][14][15][16][17]. DDAVP dosing was the standard 0.3 lg kg )1 in all patients except in the first experience by Mannucci, who utilized 0.5 lg kg )1 [5].…”
Section: Resultsmentioning
confidence: 99%
“…Additional adverse events included tachyphylaxis described in one patient [11]. Antifibrinolytic agents were utilized in 72 patients (50%) [5,[9][10][11][12][13][14]16,19]. Dosing and frequency varied widely.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 20 patients (28%) had documented concomitant disorders (table 2). 4,6,7,17,19,21,23,25 In addition to desmopressin, 24 patients received at least 1 concomitant medication (table 3). 2, 3, 6, 9, 11, 19 -22, 25 Symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…The fact that almost a third (28%) of patients suffered from concomitant disorders should lead to the careful use of desmopressin. 4,6,7,17,19,21,23,25 When a clear link to water homeostasis can be established (eg diarrhea) desmopressin should be used with extreme caution.…”
Section: Resultsmentioning
confidence: 99%
“…More serious side-effects include fluid retention, hyponatremia and seizures. 36 It has been suggested that desmopressin is dangerous in children under 18 months old 37 as there is increased risk of cerebral irritation. However, Revel-Vilk et al 30 would advocate the use of desmopressin in this age group where there is a reasonable chance of benefit and that fluid intake be minimized.…”
Section: Desmopressinmentioning
confidence: 99%